2014
DOI: 10.5430/ijba.v5n2p71
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the HRM-Performance Link: A Literature Review on the HRM Strategy Formulation Process

Abstract: Although most studies in strategic human resource management literature have deeply examined the relationship between HRM and performance, extant literature has shown mixed and inconclusive results. In general, researchers have usually focused on how organizations implement their HRM strategies, using the traditional 'content perspective'. In this sense, SHRM literature has paid less attention to the antecedents of these strategies and the internal dynamic by which HRM systems are defined. Therefore, consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…One essential organizational system that has an impact on the organization as a whole is human resource management (HRM). Studies have shown the diverse functions and roles of HRM within an organization (Armstrong, 2009; Ulrich, 1997), including some that require a strategic and coherent approach to managing the organization’s members (Armstrong, 2009; García-Carbonell et al , 2014). Integration of functions, subsystems or projects helps prevent the occurrence of organizational “islands” and lack of coordination (Sampaio et al , 2012; Turkulainen et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One essential organizational system that has an impact on the organization as a whole is human resource management (HRM). Studies have shown the diverse functions and roles of HRM within an organization (Armstrong, 2009; Ulrich, 1997), including some that require a strategic and coherent approach to managing the organization’s members (Armstrong, 2009; García-Carbonell et al , 2014). Integration of functions, subsystems or projects helps prevent the occurrence of organizational “islands” and lack of coordination (Sampaio et al , 2012; Turkulainen et al , 2015).…”
Section: Introductionmentioning
confidence: 99%